"أثر السيولة والربحية على أمان المصارف التجارية الخاصة السورية" - مرهج منذر; دنوره نور (مجلة جامعة تشرين للبحوث والدراسات العلمية- سلسلة العلوم الاقتصادية والقانونية, 2018)
This study aimed study the impact of both liquidity and profitability on the banking safety of the Syrian private commercial banks and their relationship with them. The needed data were collected from two main sources: the financial statements, and the disclosures of the privet commercial banks listed in the Damascus Securities Exchange, the studied sample consists of all listed (11) banks, and the Damascus Securities Exchange reports for the period (2009-2016). For the purposes of analysis, the Pearson correlation coefficient and the multiple linear regression model were used to study the relationship between liquidity and profitability with the banking safety and their impact on it. The results of the study showed that, there is a statistically significant positive correlation between the liquidity ratios (total liquid and semi-liquid assets/ total deposits; total liquid assets/ total deposits; total liquid assets/ total assets) and banking safety in Syrian private commercial banks, there is a statistically significant positive correlation between the profitability ratio (Return On Assets; Return On Equity) and banking safety in Syrian private commercial banks. The study recommended the need to maintain high and good levels of banking safety in Syrian private commercial banks to exceed 20%, and the need to maintain good levels of liquidity and attention in investing shareholders’ funds and all bank assets due to their important role in raising the level of banking safety in Syrian private commercial banks, and the study recommended benefiting from the models reached by the study and developing it to more sophisticated models by relying on data for longer periods of time. هدف البحث إلى دراسة تأثير كل من السيولة والربحية على الأمان المصرفي للمصارف التجارية الخاصة السورية وعلاقتهما به. وقد تمّ جمع البيانات اللازمة لذلك من خلال مصدرين رئيسين: القوائم المالية، وإفصاحات المصارف التجارية الخاصة المدرجة في سوق دمشق للأوراق المالية، وعددها أحد عشر مصرفاً مثلت عينة الدراسة، وتقارير سوق دمشق للأوراق المالية خلال الفترة (2009- 2016). وبغرض التحليل، فقد تمّ استخدام معامل الارتباط بيرسون ونموذج الانحدار الخطي المتعدد لدراسة علاقة كل من السيولة والربحية بالأمان المصرفي وتأثيرهما عليه. وقد أظهرت نتائج البحث وجود علاقة ارتباط طردية قوية ذات دلالة إحصائية بين نسب السيولة (إجمالي الأصول السائلة وشبه السائلة/ إجمالي الودائع؛ إجمالي الأصول السائلة/ إجمالي الودائع؛ إجمالي الأصول السائلة/ إجمالي الأصول) والأمان المصرفي في المصارف التجارية الخاصة السورية. كما أظهرت وجود علاقة ارتباط طردية مقبولة ذات دلالة إحصائية بين نسب الربحية (العائد على الأصول؛ العائد على حقوق الملكية) والأمان المصرفي في المصارف التجارية الخاصة السورية. وقد أوصى البحث بضرورة الحفاظ على مستويات مرتفعة وجيدة من الأمان المصرفي في المصارف التجارية الخاصة السورية بحيث تزيد عن نسبة 20%، وضرورة الحفاظ على مستويات جيدة من السيولة والاهتمام باستثمار أموال المساهمين وكافة أصول المصارف نظراً لدورهما المهم في رفع مستوى الأمان المصرفي في المصارف التجارية الخاصة السورية، كما أوصى البحث بالاستفادة من نموذجي البحث الذين توصل إليهما وتطويرهما إلى نماذج أكثر تطوراً من خلال الاعتماد على بيانات لفترات زمنية أطول.